2021
DOI: 10.1080/09553002.2021.1981556
|View full text |Cite
|
Sign up to set email alerts
|

A novel oral formulation of BIO 300 confers prophylactic radioprotection from acute radiation syndrome in mice

Abstract: Purpose: Exposure to high doses of ionizing radiation can result in hematopoietic acute radiation syndrome (H-ARS) and delayed effects of acute radiation exposure (DEARE). There is no radiation medical countermeasure (MCM) approved by the U.S. Food and Drug Administration which can be used prior to radiation exposure to protect exposed individuals. Different formulations containing synthetic genistein (BIO 300) are being developed to counter the harmful effects of radiation exposure. Materials and methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The significant DEGs identified in the MSD cohort at 8 to 12 hours after the sixth dose are visualized in volcano plots relative to all other genes (>18 000 genes) (Figure 4C). The number of DEGs following the final dose in the MSD study highlights the importance of administering multiple doses for optimal radioprotection as observed in mouse studies 11 . Temporal changes in gene expression were analyzed by comparing the Log2 fold change (Log2FC) in expression relative to baseline of significantly DEGs at multiple timepoints in the MSD study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant DEGs identified in the MSD cohort at 8 to 12 hours after the sixth dose are visualized in volcano plots relative to all other genes (>18 000 genes) (Figure 4C). The number of DEGs following the final dose in the MSD study highlights the importance of administering multiple doses for optimal radioprotection as observed in mouse studies 11 . Temporal changes in gene expression were analyzed by comparing the Log2 fold change (Log2FC) in expression relative to baseline of significantly DEGs at multiple timepoints in the MSD study.…”
Section: Resultsmentioning
confidence: 99%
“…Genistein functions as a selective estrogen receptor beta (ERβ) agonist and has a 2000‐fold higher selectivity for ERβ compared to ER‐alpha (ERα) 4 . Nonclinical studies in mice exposed to lethal total‐body irradiation (TBI) show that prophylactic treatment with genistein HME for 6 consecutive days significantly improves survival 11 . Additionally, studies with aqueous nanosuspensions of genistein formulated for oral or parental administration have demonstrated prophylactic efficacy for H‐ARS in mice 4,12,13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BIO 300 OP is a solid dosage, free-flowing dry powder, which is in contrast to previous BIO 300 formulations which are aqueous nanosuspensions. Our initial study using BIO 300 OP formulation has demonstrated that it has efficacy in a murine H-ARS model equivalent to that of BIO 300 OS 24 , 40 . The purpose of this study was to determine the pharmacokinetics (PK) of a single dose of BIO 300 OP and the associated metabolic changes in an NHP model.…”
Section: Introductionmentioning
confidence: 99%
“…This oral formulation, BIO 300 Oral Powder (BIO 300 OP), is produced by hot-melt extrusion. Our initial study using BIO 300 OP formulation has demonstrated that it has e cacy in a murine H-ARS model equivalent to that of BIO 300 OS 24,39 . The purpose of this study was to determine the pharmacokinetics (PK) of a single dose of BIO 300 OP and the associated metabolic changes in an NHP model.…”
Section: Introductionmentioning
confidence: 99%